Overview of family behavior and community stigma towards mental disorders in west Sumba Regency - Belarminus, Petrus; Ora, Anderias T.; Saghu, Maria M.P.; Agustine, Uly; Santoso, Shelfi Dwi Retnani Putri; Riti, Desy Natalia (Institute of Computer Science (IOCS), 2025)
Stigma and discrimination exacerbate the psychological conditions of individuals with mental illness, discouraging them from seeking professional help and complicating their recovery. This stigma can lead to severe consequences, including shackling and suicide. Families who understand the needs of people with mental illness play a crucial role in providing support and accelerating recovery. This qualitative research was conducted in the Puuweri and Weekerou Puskesmas work areas of West Sumba Regency in June 2024, involving 18 participants, including 10 families of individuals with mental illness and 8 community leaders, selected through purposive sampling. Data collection employed interviews, field notes, and sound recordings, following ethical protocols. The study identified significant challenges in mental health management in Sumba, including limited health facilities and medical personnel. External support from health centers, foundations, and traditional healers emerged as vital in assisting families and ensuring proper treatment. Despite reliance on traditional beliefs, these external resources act as crucial bridges for effective care. The findings of this study offer valuable insights for policy development to address mental health challenges in West Sumba, emphasizing the importance of collaborative efforts between families, healthcare providers, and community resources.